Upaya Guru Dalam Pembiasaan Shalat Lima Waktu Murid TPQ Asy Syarif - Bariroh, Azmil Mukhibbatul; Hidayah , Siti Abidatul (Amaliyatu Tadris, 2022)
The Purpoe of this research is to find out Master’s effort ini habitating the five Times Prayer of pupils TPQ Asy Syarif. This research is a field research. This research uses descriptive ualitative reasearch is reporting describing and collecting actual information in detail about exiting symptoms, identifying problems. Wheres the data source is obtained and collected from the field. Based on the resuld of the study. It was illustrated that the efford of the TPQ teacher in the habit of praying five times for TP Asy Syarif’s Student were quete good. By using the method of practice memorizing readings and coaching prayers using the prayer diaries of TPQ Asy Syarif student in which the book contains the initials of teacher and parents to mentor the implementation of the prayer of student at TPQ Asy Syarif